56 Characterization of Pasture Management by Horse Operation Purposes in Florida. (8th March 2022) - Vasco, Carol M; Silva, Liliane; Mullenix, Kim; Dillard, Leanne L; Wickens, Carissa; Warren, Lori K
Abstract: Adequate pasture management can decrease costs related to supplemental feed in horse operations. However, the purpose of the horse operation may influence the level of pasture management applied. An online survey was conducted from 2018 to 2020 to evaluate if pasture management strategies used on Florida horse farms are associated with the purpose of the operation. This survey also provided inputs as needs assessment for educational programs in Florida and the Southeast United States. Survey data (n = 79 respondents) were submitted to descriptive analysis and Fisher's exact test. Significantly associated variables were also evaluated using multiple correspondence analysis. The primary function of the operation most reported was recreational (62%), followed by training (15%), boarding (8%), breeding (6%), and other (5%). Horses were turned out onto pasture full time (24 h/d) in 57% of operations. The purpose of the operation tended to be associated with turnout practices (P = 0.08). Multiple correspondence analysis revealed that boarding- and recreational-purpose operations tended to turn horses out full time or most of the day (12 h/d), while training facilities tended to turn horses out during the night or for a short duration (~4 h/d) during the day. As for level of pasture management, pasture establishment but no maintenance was implemented by 3% of the respondents, 9% implemented pasture establishment and maintenance, 82% performed maintenance only, and 6% did not implement any pasture management. Concerning types of pasture management, pastures were overseeded by 34% of the operations, fertilized by 57%, and continuously stocked by 52%. The purpose of the operation was not associated (P > 0.05) with the level or type of pasture management strategy. Results demonstrate that pasture management practices were implemented similarly among Florida horse operations regardless of their purpose. These results illustrate an educational need to provide information and resources for horse owners aiming to improve the adoption of best pasture management strategies and decrease feeding costs.